If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5j + 4s + 3t = 108 Solving 5j + 4s + 3t = 108 Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '-4s' to each side of the equation. 5j + 4s + -4s + 3t = 108 + -4s Combine like terms: 4s + -4s = 0 5j + 0 + 3t = 108 + -4s 5j + 3t = 108 + -4s Add '-3t' to each side of the equation. 5j + 3t + -3t = 108 + -4s + -3t Combine like terms: 3t + -3t = 0 5j + 0 = 108 + -4s + -3t 5j = 108 + -4s + -3t Divide each side by '5'. j = 21.6 + -0.8s + -0.6t Simplifying j = 21.6 + -0.8s + -0.6t
| 2+4x=5x+22 | | 26+m=47 | | 6x+2=2(x+4)-2 | | b*-3.4=30.94 | | 4=12k | | x^2-2kx+2=0 | | 93=h+15 | | 10.2y=14x-8 | | -7x-4=-8x+8 | | =x^2+18x+81 | | -49+z=-56 | | y^2+7y= | | 5y-2y=13y+20 | | 3*x+6=x+1 | | -3f=42 | | 2w^2+1w+7=0 | | 87=b+18 | | -23+k=17 | | 2+5x=-22+x | | 2(6-3x)-3(1+x)=5x | | =3z^2+2z+4 | | 2x^2+12x-1040=0 | | 5z^2+22z+21=0 | | t+17=43 | | 2x+6=-397x | | -1-4x=-5x+1 | | 2x+17=26 | | ln(3x)=y | | 2x+9y=31 | | 3/n-3/10= | | =36x^2-60xy+25y^2 | | 28=0.2n+2.5 |